Improving English Language Skills Students Of Graha Yatim Dhuafa Based On Survey Results Study Interest: Peningkatan Kemampuan Bahasa Inggris Siswa Graha Yatim Dhuafa Berbasis Hasil Survey Minat Belajar - Anindita, Rina; Agustina, Noni; Simatupang, Marhisar; Prastyani, Desy; Rahman, Taufiqur (Universitas Lancang Kuning, 2025)
Community Service Activities (PKM) carried out at Graha Yatim (GRAY) Cempaka Putih, Jakarta, aim to help students in grades 5 elementary to 2 high school to have better English language skills. The activity begins with an assessment of the English language skills as well as the interests and talents of students assisted by the GRAY orphanage in learning English. Followed by activities to improve students' English skills through the language learning application